Numerical investigation on penetration response of cylindrical corrugated core sandwich structure subjected to oblique impact - Rusdan, S.A.; Aziz, N. A.; Topa, A.; Mansor, M.N.S. (Faculty Engineering, Universiti Putra Malaysia, 2024)
Recent interest has been focused on corrugated core sandwich structures due to the corrugation structure's ability to withstand high impact and high stiffness to weight ratio. It has been widely used in automotive application. Underbody shield of vehicle experience with a diagonal impact of object from underneath. Therefore, this paper aimed to investigate the penetration response of object on cylindrical corrugated core sandwich (C3S) structure subjected to oblique impact. Numerical simulation of cylinder impactor on C3S structure is presented using LS-DYNA software. The developed model is validated using finite element (FE) model that has been published. Penetration response is measure using time displacement graph. Good correlation was found between time displacement graph of simulation study and the published model. The displacement is decreasing as the core thickness and skin thickness are increasing. The results provide insight into the oblique impact behaviour of these structures, and the knowledge of their deformation response can be applied to future development.